Study of the illogical consistencies in Beckett’s Endgame - Vincent, Sandra Marie (2011)
Through the focal point of Reductio Ad Absurdum, Endgame, highlights the absurdity that is inherent in conceiving logic. It is by highlighting what is perceived to be logical and in refuting this and showing its absurdity that Beckett addresses the difficulty in conceptualizing what is logic. Through this he identifies the inherent absurdity in logic. Endgame deals with two major concepts of free will and time. The former, deals with the fundamental concepts of life such as moral responsibility and choice whereas the latter, deals with individual’s place in time. These are essential in giving meaning to individual’s lives. Beckett’s theatre breaks down the epistemological systems of stage, dialogue, props and characterization. Through the themes of free will and endgame in chess, coupled by his RAA theatrical convention, Beckett challenges the epistemological and ontological perceptions of the audience. It is interesting to note that, if an individual follows the methodology in RAA, it is systematic and requires logic. This shows that even in expressing the absurd, there is a need to use a logical and concise approach to it. This shows the failure of Beckett in denying logic absolutely. Yet, by the same token, it strengthens his depiction of absurdity for the RAA paradigm itself is absurd. It is the failure and strength of both RAA and Beckett’s method that is vital in illustrating Beckett’s expression of the human condition.